PENGGUNAAN MEDIA PAPAN PERKALIAN UNTUK MENINGKATKAN KEMAMPUAN BERHITUNG PADA MATERI PERKALIAN DI KELAS III SDN 182/I HUTAN LINDUNG - Charolyna Pajaitan, Febrinurty; Anderson, Irzal; Gusmaulia Eka Putri, Andi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The problem behind this study is that students still have difficulty in learning multiplication and teachers have not fully used learning media in the teaching and learning process and only focus on printed books and material explanations with the lecture method. So that the multiplication ability of grade III students of SDN 182/I Protected Forest is low, which can be seen from the number of students who have not reached the criteria for achieving learning objectives (KKTP). This study aims to describe the use of multiplication board media can improve the ability of grade III students of SDN 182/I Hutan Lindung. As well as to find out how much the multiplication ability of students has increased after using the multiplication board media in the third grade students of SDN 182/I Hutan Lindung. The research method uses the Classroom Action Research (PTK) method as many as two cycles, each cycle consists of the stages of planning, implementation of actions, observation, and reflection. The subjects of the study included teachers and students in grade III, which amounted to 18 students consisting of 14 males and 4 females. Data collection techniques include tests, observations, documentation, and interviews. The results of the study show that multiplication board media can improve multiplication ability in grade III students of SDN 182/I Hutan Lindung. In addition, the use of multiplication board media in learning can be passed well, both from student activities and from the learning outcomes obtained by students have improved. The increase in students' multiplication ability was evident during the pre-cycle period where the average score of students was obtained 48.61 with learning completeness of 27.78%. After the implementation of the action in the first cycle, the average score of students was 66.11 with a learning completeness of 50%, even more increased in the second cycle with an average student score of 87.22 which the completeness of learning students reached 94.44%. The success of classical learning completeness has exceeded the target of 70%, so in the second cycle it was stopped. The results obtained have met the predetermined success indicators